2015
DOI: 10.1155/2015/761501
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriCagA Suppresses Apoptosis through Activation of AKT in a Nontransformed Epithelial Cell Model of Glandular Acini Formation

Abstract: H. pylori infection is the most important environmental risk to develop gastric cancer, mainly through its virulence factor CagA. In vitro models of CagA function have demonstrated a phosphoprotein activity targeting multiple cellular signaling pathways, while cagA transgenic mice develop carcinomas of the gastrointestinal tract, supporting oncogenic functions. However, it is still not completely clear how CagA alters cellular processes associated with carcinogenic events. In this study, we evaluated the capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…MCF-10A cells are human mammary epithelial cells that were obtained from the American Type Culture Collection (ATCC CRL-10317, Manassas, VA, USA). MCF-10A three-dimensional (3D) or monolayer (2D) cultures were performed as previously reported by us and Debnath et al [ 47 , 51 ]. For infection assays, MCF-10A cells were seeded at 3000 cells/cm 2 and cultured for 48 hrs to reach 70% subconfluency and then switched to DMEM-F12 without fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCF-10A cells are human mammary epithelial cells that were obtained from the American Type Culture Collection (ATCC CRL-10317, Manassas, VA, USA). MCF-10A three-dimensional (3D) or monolayer (2D) cultures were performed as previously reported by us and Debnath et al [ 47 , 51 ]. For infection assays, MCF-10A cells were seeded at 3000 cells/cm 2 and cultured for 48 hrs to reach 70% subconfluency and then switched to DMEM-F12 without fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…We recently found that CagA induces anoikis resistance through activation of the AKT signaling pathway [ 47 ]. AKT is also an important mediator of EMT through inactivation of glycogen synthase kinase 3 β (GSK3 β ), a critical negative regulator of β -catenin.…”
Section: Introductionmentioning
confidence: 99%
“…As in many other infections, H. pylori triggers the downregulation of p53 protein by which the bacterium blocks apoptosis one of the main defensive mechanism in infected cells (23,24). This protective function of p53 is also impaired in many forms of cancer (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…This protective function of p53 is also impaired in many forms of cancer (25,26). (8,23,24), by activating pathways that are already present in cells (14). Yet, this has possibly lethal consequences for the host as the damage of p53, the central "guardian of the genome", upsurges the risk of mutant cells to survive and develop into cancer cells (25,26) Numerous bacterial contagions are now supposed to be a factor in cancer development but their association is not so decisively proven as for H. pylori, which can induce chronic gastritis, gastric ulcer and finally lead to cancer development ( 7 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation